Estudo de conceitos de astronomia em uma comunidade remanescente de quilombos no Recôncavo baiano - Bastos, Paulo Marcos Santiago (2019)
Concepts and practical actions possibly oriented by astronomical aspects, such as seasons, lunations and tidal effect was studied and discussed, from the perspective of Ethnoastronomy. It took place in a remnant quilombo community in the Bahia Recôncavo, which basically survives fisheries and subsistence agriculture. It was sought to identify how these concepts would be found as previous conceptions in a formal school, a space in which a didactic sequence (SD) was proposed. The aim was following-up the Conceptual Evolution (EL-HANI; MORTIMER, 2007), referencing to Significant Learning Theory (MOREIRA, 1999).A first phase took place in the community of Engenho da Ponte, Cachoeira, Bahia, based on meetings with the social actors themselves and the collection of their reports.The second phase consisted on the application of SD in the Eraldo Tinoco State College, in the city of Santiago do Iguape, also in Cachoeira, Bahia.The educational product proposed in this work is the aforementioned Didactic Sequence (SD), with a view to its constitution as a pedagogical reference to teachers of the quilombola community school, to teachAstronomy concepts.